Mitochondrial DNA depletion syndrome and its cardiac complication - Bao, Shengfang; Ye, Jiajun; Zhou, Jiaqi; Zheng, Chen; Xu, Yuejuan; Chen, Sun (Frontiers in Cardiovascular Medicine, 2025)
Mitochondrial depletion syndrome (MTDPS) is a heterogeneous group of genetic disorders characterized by a significant reduction in mitochondrial DNA (mtDNA) copy number, leading to the impaired mitochondrial function. The pathogenesis of MTDPS includes impaired mtDNA replication, damaged nucleotide metabolism and dysregulated mitochondrial dynamics. Due to its high energy demands, the heart is sensitive to the mitochondrial dysfunction. And the energy deficiency caused by the MTDPS contributes to the development of the mitochondrial cardiomyopathy. In this review, we summarize the cardiac phenotypes in the MTDPS, and the role of the mitochondrial injury in the myocardial damage. In specific, the association of the MTDPS-causing genes and their cardiac phenotypes are detailed. Moreover, the current treatment strategies for MTDPS are summarized. This review aims to integrate the current knowledge on the MTDPS and its cardiac phenotypes in order to provide insights for the further research and the clinic management.